If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3x+3=15+5x
We move all terms to the left:
3x+3-(15+5x)=0
We add all the numbers together, and all the variables
3x-(5x+15)+3=0
We get rid of parentheses
3x-5x-15+3=0
We add all the numbers together, and all the variables
-2x-12=0
We move all terms containing x to the left, all other terms to the right
-2x=12
x=12/-2
x=-6
| x=16=16+16+2x-3x | | 8(((2x+5)/5)+x-3)=61 | | 4x-6=2x+40 | | 90+90+(2x+4)+(3x-29)=306 | | 90+90+(2x+4)+(3x-29)=36 | | 0.554x+2=6.05 | | X^2-14x-83=4 | | .5x+12=2x+27 | | 7/4=-5x | | 6a+7(6)=a-2 | | -3z=8-2 | | 0.48x-1.52=-506 | | 2x+5=37.5 | | 42=4x^2 | | x+5=37.5 | | -226=-12x+2 | | 19=x-(-8) | | 6/x=1,7 | | 15+x=71 | | 2=-12x+2 | | -7x-2=3x+10 | | x^-x-110=0 | | 2x+25=95 | | 12/x+2+8=10 | | 9=b-7/5 | | X+2y(-4)=8 | | 3x^+7x-5=0 | | 3|4x-2|+5=41 | | -3x-5x-17=3 | | 5=3+0.2y | | 5=3+0,2y | | 23+c=56 |